Promoted activity of porous silica coated Ni/CeO2ZrO2 catalyst for steam reforming of acetic acid. (24th August 2017) - Zhao, Xiaoyong; Xue, Yaping; Yan, Changfeng; Huang, Ying; Lu, Zhuoxin; Wang, Zhida; Zhang, Liang; Guo, Changqing
Abstract: Porous silica coated Ni/CeO2 ZrO2 catalysts were synthesized for steam reforming of acetic acid. The silica coated Ni/CeO2 ZrO2 catalyst showed a significantly enhanced activity (95% acetic acid conversion) than the Ni/CeO2 ZrO2 catalysts (62% acetic acid conversion) at a low temperature (550 °C). Interaction between Ni/CeO2 ZrO2 and silica layer was proved to be a crucial role on enhancing of catalytic activities. Further characterization (XPS, H2 -TPR) indicates this interaction facilitates the steam reforming reaction and raises the selectivity of CO by modifying the surface Ni electronic structure. In addition, the coated catalyst also exhibited a good stability and no obvious deactivation was detected at 550 °C and 600 °C within 30 h. Highlights: The intrinsic activity of Ni is greatly promoted by coating a SiO2 layer. The TOF of Ni is increased by 8.3 times after coating with SiO2 layer. Interaction of Ni and SiO2 plays a key role on enhancing of Ni intrinsic activity. The interaction of Ni and SiO2 leads to partly oxidation of surface Ni atoms. The partly oxidized Ni atom is more active than normal Ni atom.